Policy Strategy to Improve Human Development Index in Kayong Utara District - Aryada, Kasdi Tri; Martoyo; Sihaloho, Nahot Tua Parlindungan (Ilomata International Journal of Social Science, 2024)
This research aims to analyze and describe the problem of a weak human development index in North Kayong Regency using the Public Policy, Governance, and Human Development approaches. The phenomenon that occurs is important to discuss for three reasons: education is still low, health and supporting facilities are still lacking, and the standard of living of the community is still lacking. The method used in the research is the descriptive qualitative method. The results of this study indicate that the low HDI of North Kayong Regency is influenced by three indicators. First, education in North Kayong Regency is low, this is also influenced by the mindset of the community regarding the importance of education which is still lacking, and the weak government support regarding supporting facilities and infrastructure, especially in the Karimata Islands District area. Second, public health which is still lacking makes people vulnerable to diseases that can also affect a person's lifespan. The weakness of health improvement programs and the lack of health facilities and personnel are obstacles in the process of implementing health programs in North Kayong Regency. Third, community livelihoods in North Kayong Regency are also still lacking, such as high unemployment and poverty.